Pharmacokinetic-pharmacodynamic integration and resistance of tiamulin against Mycoplasma hyopneumoniae in an in vitro dynamic model. (October 2020) - Huang, Zilong; Xia, Xirui; Mao, Chunxiao; Gu, Xiaoyan; Shen, Xiangguang; Yang, Hong; Ding, Huanzhong
Abstract: Mycoplasma hyopneumoniae is the major pathogen of enzootic pneumonia in pigs. We established an in vitro dynamic model to investigate the relationship between the pharmacokinetic and pharmacodynamic (PK-PD) parameters of tiamulin against M. hyopneumoniae . Static time-killing curves showed that mycoplasmacidal activity (reduced 3.0 log10 (CFU/mL)) was achieved during 48 h when the drug concentration was 8 MIC, and with a maximum kill rate of 0.072/h. In dynamic time-killing studies, only the dose-fractionated regimen achieved mycoplasmacidal activity when drug concentration was 1.44 and 1.92 mg/L. The duration of post antibiotic effect (PAE) at 1 × MIC was 6.27 ± 0.11 h, and prolonged as the concentration of tiamulin increased. The cumulative percentage of time over a 48-h period that the drug concentration exceeds the MIC (%T > MIC) was the best PK-PD parameter to predict the antimicrobial activity of tiamulin against M. hyopneumoniae ( R 2  = 0.98). Tiamulin showed time-dependent and prolonged PAE activity. Two strains of M. hyopneumoniae (M1, M2) had acquired resistance to tiamulin as well as to valnemulin, tylosin and amikacin. The genome of strain ATCC 25934 was used as a reference for gene-mutation analysis. For strains M1 and M2, a A2058C mutation occurred in domain V of 23S rRNA. These data showed that tiamulin had excellent efficacy and concentration-dependent characteristics against M. hyopneumoniae in vitro . The lower dose was not safe because it could lead to enrichment of resistant bacteria. Highlights: Mycoplasma hyopneumoniae (MH) is the major pathogen of enzootic pneumonia in pigs. Associations between the PK–PD parameters of tiamulin against MH were studied. AUC0–48 h /MIC was the best PK–PD parameter to predict tiamulin's activity against MH. Tiamulin had excellent efficacy and concentration-based features against MH in vitro . A low dose of tiamulin was not safe because it could lead to resistant bacteria.